Shiga Toxins Induce, Superinduce, and Stabilize a Variety of C-X-C Chemokine mRNAs in Intestinal Epithelial Cells, Resulting in Increased Chemokine Expression - Thorpe, Cheleste M. (American Society for Microbiology, 2001)
Exposure of humans to Shiga toxins (Stxs) is a risk factor for hemolytic-uremic syndrome (HUS). Because Stx-producing Escherichia coli (STEC) is a noninvasive enteric pathogen, the extent to which Stxs can cross the host intestinal epithelium may affect the risk of developing HUS. We have previously shown that Stxs can induce and superinduce IL-8 mRNA and protein in intestinal epithelial cells (IECs) in vitro via a ribotoxic stress response. We used cytokine expression arrays to determine the effect of Stx1 on various C-X-C chemokine genes in IECs. We observed that Stx1 induces multiple C-X-C chemokines at the mRNA level, including interleukin-8 (IL-8), GRO-α, GRO-β, GRO-γ, and ENA-78. Like that of IL-8, GRO-α and ENA-78 mRNAs are both induced and superinduced by Stx1. Furthermore, Stx1 induces both IL-8 and GRO-α protein in a dose-response fashion, despite an overall inhibition in host cell protein synthesis. Stx1 treatment stabilizes both IL-8 and GRO-α mRNA. We conclude that Stxs are able to increase mRNA and protein levels of multiple C-X-C chemokines in IECs, with increased mRNA stability at least one mechanism involved. We hypothesize that ribotoxic stress is a pathway by which Stxs can alter host signal transduction in IECs, resulting in the production of multiple chemokine mRNAs, leading to increased expression of specific proteins. Taken together, these data suggest that exposing IECs to Stxs may stimulate a proinflammatory response, resulting in influx of acute inflammatory cells and thus contributing to the intestinal tissue damage seen in STEC infection.